The effect of pyrolysis conditions on the composition of Chinese Jimsar shale oil using FT-IR, 1H-NMR and 13C-NMR techniques - Hao Lu; Luwei Pan; Yue Guo; Fangqin Dai; Shaohui Pei; Jianning Huang; Shuang Liu (Oil Shale, 2022)
Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance (NMR) were used to characterize the functional groups and structural parameters of shale oil obtained from the pyrolysis of Chinese Jimsar oil shale under different process conditions: pyrolysis temperature 480, 500, 520, 550 Â°C, residence time 10, 20, 30, 40 min and heating rate 2, 5, 8, 10 Â°C/min. The results show that the main substances in shale oil are aliphatic components, mainly âCH2 with antisymmetric stretching vibrations. The longest aliphatic chain of shale oil is at the pyrolysis temperature of 520 Â°C, the residence time of 20 min and the heating rate of 5 Â°C/min. The relative content of aromatics in shale oil is less than 20%. Di-substitution is the main substitution mode of the benzene ring, accounting for more than 45%. The results also indicate that the relative content of oxygen-containing functional groups (CâO and C=O) is much smaller than that of âCH2 and âCH3, while the relative content of CâO is higher than that of C=O functional groups. The increase of temperature, heating rate and residence time contributes to the formation of aromatic compounds.